Fund Conditionality : Evolution of Principles and Practices - Guitian, Manuel (Washington, D.C. : International Monetary Fund, 1981)
This paper examines the principles and practices of conditionality as they have evolved and as they are currently applied. The paper discusses the rationale of the concept of conditionality and brings out its theoretical underpinnings as well as its economic policy implications. The paper traces the practices for conditionality's implementation that have been developed in the IMF over more than three decades to assist members in adjusting to an increasingly difficult and complex environment. The paper also discusses a series of issues that have arisen in the context of the application of conditionality.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet